Evaluation of Burnout Syndrome Prevalence in Medical Students - Rodrigues,Camila Serra (2020)
Abstract: Introduction: Burnout Syndrome (BS) is related to chronic occupational stress, present in the life of medical students. This syndrome comprises three basic dimensions: I- emotional exhaustion; II- increased mental distancing from the work itself or feelings of negativism and cynicism related to the work itself; and III - reduced professional effectiveness. This study aims to assess the prevalence, risk factors for the development and symptoms associated with Burnout Syndrome in medical students from a district college, in addition to establishing a profile of students with a higher risk of having a BS diagnosis. Method: This is a cross-sectional observational study. The Maslach Burnout Inventory (MBI) - Student Survey questionnaire, specific version for students, which is a questionnaire of sociodemographic factors, one of predictive factors and another of possible somatic symptoms associated with BS were applied. The sample was obtained by convenience and its representativeness was calculated in relation to the total number of students. A student was considered to be at moderate or high risk of developing BS when they had one or two altered BS dimensions, respectively. Results: 67.11% of the total students regularly enrolled from the 1st to the 6th year of the medical course answered the questionnaires. Of the total sample, 80.63% of male students and 81.06% of female students were identified as having a high or moderate risk for BS. The sociodemographic factors associated with the risk of developing BS were: age, who the student lives with, having children and doing paid work. The most statistically significant predictor was the self-management of tasks proposed by the Medical School. Conclusion: The prevalence of high risk and diagnosis of BS found among medical students was 26.44% and 3.95%, respectively. Differences were identified between the high-risk profiles for female and male students.